Revealing the Legal Implications of Post-Eiddah Reconciliation from the Perspective of Maslahah - Kartini, Aisyah; Sulfinadia, Hamda; Mahmut, Rami İbrahim (Program Studi Hukum Keluarga Islam, 2025)
The end of the marriage bond in Islamic law can occur through two forms of divorce, namely divorce raj'i (which allows reconciliation during the iddah period) and divorce ba'in (which does not allow reconciliation without a new contract). This study aims to examine in depth the implications of maslahah on the phenomenon of reconciliation of married couples after the end of the iddah period, especially in the social and cultural context of Indonesian society. The research method used is descriptive-analytical with a juridical normative approach, which is based on a literature study of classical and contemporary sources of Islamic law, as well as applicable laws and regulations. The data is analyzed qualitatively to reveal the requirements, procedures, and rights and obligations that surround the process of rujuk or post-iddah reconciliation. The results show that even though the iddah period has ended, there is legal space that allows for a remarriage contract as a form of reconciliation, as long as the shar'i requirements are met. The views of the imams such as Hanafi, Maliki, Shafi'i and Hanbali provide diverse but complementary perspectives in assessing the validity of post-iddah reconciliation. The discussion emphasizes the importance of considering maslahah in the practice of reconciliation, in order to protect the interests of both parties and maintain social stability. Thus, reconciliation after the iddah period can not only be considered legally valid, but also beneficial in the context of the benefit of the people and does not conflict with the principles of state law.